Proteomic responses to nanoparticulate and ionic silver in aquatic fungi - Barros, Diana Cláudia Martins Costa (2016)
Enhanced use of silver nanoparticles (AgNPs) has inevitably resulted in their release into aquatic environments raising concern about the risk to aquatic biota and related ecological functions. Functional proteomics is an emerging technology that provides high-throughput analyses augmenting measurements of direct and highly sensitive responses at the cellular and sub-cellular levels. The impacts of AgNPs and its ionic precursor (Ag+ in AgNO3) at low exposure concentrations (close to environmental realism) on a fungal strain isolated from a non-polluted stream were assessed based on the variations in the overall proteome as well as in the activity of selected antioxidant enzymes. A total of 352 proteins were identified, but only 151 proteins were responsive (significantly up- or down-regulated relative to control) of which 65% presented matching alterations. Out of these 151 proteins, 62% increased abundance under stress induced by AgNPs and 56% under stress induced by Ag+. Exposure to both forms of silver induced proteins related to stress response, in particular, antioxidant enzymes. The antioxidant enzymatic responses were consistent with the proteomic responses, suggesting that the ability to initiate an efficient antioxidant response is essential for the fungus to cope with Ag-induced toxicity. Moreover, several proteins involved in the metabolism of carbohydrates, amino acids and lipids were altered. This evidence may reflect the need of generating energy to support the cellular defense mechanisms. Some of the significantly altered proteins were associated with the correct folding of nascent and stress accumulated misfolded proteins or degradation of transiently denatured and unfolded proteins preventing their aggregation. Others were related to the regulation of translation suggesting a compromised protein synthesis system. Overall, the functional proteomic approach can be useful to expand the knowledge on silver-induced stress responses in aquatic fungi